Myotendinous Junction: Exercise Protocols Can Positively Influence Their Development in Rats - Neto, Jurandyr Pimentel [UNESP] (2022)
The myotendinous junction (MTJ) is an interface that different stimuli alter their morphol-ogy. One of the main stimuli to promote alterations in the MTJ morphology is physical exercise. The present study aimed to investigate the morphology and molecular MTJ adaptations of biceps brachii muscle in adult Wistar rats submitted to different ladder-based protocols. Forty Wistar rats (90 days old) were divided into four groups: Sedentary (S), Climbing (C), Overload Climbing (OC), Climbing, and Overload Climbing (COC). The results of light microscopy demonstrated the cell and collagen tissue reorganization in the experimental groups. The sarcomeres lengths of different regions showed a particular development according to the specific protocols. The sarcoplasmic invagina-tions and evaginations demonstrated positive increases that promoted the myotendinous interface development. In the extracellular matrix, the structures presented an increase principally in the COC group. Finally, the immunofluorescence analysis showed the telocytes disposition adjacent to the MTJ region in all experimental groups, revealing their network organization. Thus, we concluded that the different protocols contributed to the morphological adaptations with beneficial effects in distinct ways of tissue and cellular development and can be used as a model for MTJ remodeling to future proteomic and genetic analysis.